First Principles Calculations on The Electronic and Optical Properties of Zincblende Bxga1-Xas and Bxin1-Xas Semiconductor Alloys. - Amrane, N.; Benkraouda, Maamar (JOURNAL OF ADVANCES IN PHYSICS, 2017)
A theoretical study of the electronic and optical properties of zincblende BxGa1-xAs and BxIn1-xAs semiconductor alloys is presented, using the full potential linearized augmented plane wave method. In this approach, the generalized gradient approximation was used for the exchange correlation potential. Ground state properties such as lattice parameter and band structure are calculated as a function of the mole fraction. We have also analyzed the optical properties (refractive index, dielectric function, real and imaginary), the 4x4 Kanes interaction matrix is calculated in order to ease simulations of optoelectronic devices. The results have been discussed in terms of previously existing experimental and theoretical data, and comparisons with similar compounds have been made.